Risk perceptions and public debates on climate change: a conceptualisation based on the theory of a functionally-differentiated society - Rhomberg, Markus (MedieKultur: Journal of media and communication research, 2010)
Mass media and its mechanisms of production and selection play a crucial role in the definition of climate change risks. Different form of logic in the political, scientific and media systems are vital aspects in the public debate on this issue. A theoretical analysis of these aspects needs a framework in terms of social theory: Luhmann’s concept of a functionally-differentiated society and the mechanisms of structural couplings could help to understand the relations and interplay of these systems in the climate-debate. Based on this framework and various empirical studies, this paper suggests: different logics lead to different climate-definitions in science, politics and mass media. Climate change became interesting, but not until it was located in the political decision-making process. Climate issues become publicly interesting, when they are clear, contentious and can be linked to Elite-Persons. In contrast to scientific communication, news media make great efforts to be clear and definite in their communications.